Intonations: A Social History of Music and Nation in Luanda, Angola, from 1945 to Recent Times, Marissa J. Moorman, Ohio University Press, 2008, 320 pp., CD, Paperback: 978-0-8214-1824-6. - Erlmann, Veit (International Library of African Music, 2009)
pages: 164-166
Keywords: Music; African Music; Angola; Luanda; Social History